2016
DOI: 10.1155/2016/9501410
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine Differentiation in Breast Cancer: Clinicopathological Significance of Bcl-2 Positive Solid Papillary Carcinoma

Abstract: Solid papillary carcinoma (SPC) is considered a rare malignant breast tumor. Maluf and Koerner first reported this disease entity as a special type of ductal carcinoma in situ with several characteristic histopathological features, including low-grade cellular atypia, intracellular or extracellular mucin deposition, and solid papillary growth pattern, as well as neuroendocrine differentiation. The present paper describes a case of SPC with bcl-2 expression, which is known as a marker for malignancy of neuroend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…Two of the SPC cases with NE differentiation in our series were pure SPC, and 13 cases with invasive breast carcinoma (five cases MC, five cases IC-NST, three cases IC-NST + MC) developed on an SPC backround. SPC usually arises in the seventh or eighth decade and has a better prognosis than other breast cancers (13,14). Concordantly, the mean age of patients with SPC in our series was 62.…”
Section: U N C O R R E C T E D P R O O Fsupporting
confidence: 80%
See 2 more Smart Citations
“…Two of the SPC cases with NE differentiation in our series were pure SPC, and 13 cases with invasive breast carcinoma (five cases MC, five cases IC-NST, three cases IC-NST + MC) developed on an SPC backround. SPC usually arises in the seventh or eighth decade and has a better prognosis than other breast cancers (13,14). Concordantly, the mean age of patients with SPC in our series was 62.…”
Section: U N C O R R E C T E D P R O O Fsupporting
confidence: 80%
“…The most common form of NE breast tumor-solid papillary carcinoma (SPC) and mucinous carcinoma (MC) is a suitable example of diagnostic and conceptual challenges with NET (8,13,14). However, SPC is a distinctive clinico-pathological entity that often expresses NE markers.…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%
See 1 more Smart Citation
“…Further discussion is warranted regarding the proliferative activity of GP. Previous studies ( 4 , 9 ) have shown that GP has no significant mitotic figures or Ki-67 protein, tumor protein p53, and B-cell lymphoma two immunoexpression, which are prognostic factors for several types of NETs ( 40 42 ), irrespective of the presence of LNM. Thus, general immunohistochemical prognostic factors in NETs are not useful for assessing the malignant potential of GP tumors.…”
Section: Discussionmentioning
confidence: 90%
“…Meanwhile, what is intriguing for us is that no significant correlations were identified between the Ki-67 labeling index and any parameter (age, sex, the maximum tumor diameter, venous invasion, lymphatic invasion, MVD, LMVD, and lymph node metastasis). In general, Ki-67 labeling index is regarded as a prognostic factor for many neoplasms [ 7 , 28 33 ]. However, we wish to emphasize that Ki-67 labeling index is not an absolute prognostic factor in hindgut NET cases with the relatively low level of proliferative activities.…”
Section: Discussionmentioning
confidence: 99%